Abating N in Nordic agriculture - Policy, measures and way forward. (15th April 2019) - Hellsten, Sofie; Dalgaard, Tommy; Rankinen, Katri; Tørseth, Kjetil; Bakken, Lars; Bechmann, Marianne; Kulmala, Airi; Moldan, Filip; Olofsson, Stina; Piil, Kristoffer; Pira, Kajsa; Turtola, Eila
Abstract: During the past twenty years, the Nordic countries (Denmark, Sweden, Finland and Norway) have introduced a range of measures to reduce losses of nitrogen (N) to air and to aquatic environment by leaching and runoff. However, the agricultural sector is still an important N source to the environment, and projections indicate relatively small emission reductions in the coming years. The four Nordic countries have different priorities and strategies regarding agricultural N flows and mitigation measures, and therefore they are facing different challenges and barriers. In Norway farm subsidies are used to encourage measures, but these are mainly focused on phosphorus (P). In contrast, Denmark targets N and uses control regulations to reduce losses. In Sweden and Finland, both voluntary actions combined with subsidies help to mitigate both N and P. The aim of this study was to compare the present situation pertaining to agricultural N in the Nordic countries as well as to provide recommendations for policy instruments to achieve cost effective abatement of reactive N from agriculture in the Nordic countries, and to provide guidance to other countries. To further reduce N losses from agriculture, the four countries will have to continue to take different routes. In particular, some countries will need new actions if 2020 and 2030 National Emissions Ceilings Directive (NECD) targets are to be met. Many options are possible, including voluntary action, regulation, taxation and subsidies, but the difficulty is finding the right balance between these policy options for each country. The governments in the Nordic countries should put more attention to the NECD and consult with relevant stakeholders, researchers and farmer's associations on which measures to prioritize to achieve these goals on time. It is important to pick remaining low hanging fruits through use of the most cost effective mitigation measures. We suggest that N application rate and its timing should be in accordance with the crop need and carrying capacity of environmental recipients. Also, the choice of application technology can further reduce the risk of N losses into air and waters. This may require more region-specific solutions and knowledge-based support with tailored information in combination with further targeted subsidies or regulations. Highlights: The four Nordic countries have different approaches on agricultural N flows and mitigation measures. Most countries will need new actions if National Emissions Ceilings Directive targets are to be met. A solely voluntary and economic approach may not promote the necessary changes needed. Tailored information and support in concert with targeted subsidies and regulations may be required. It is important to apply the most cost effective mitigation measures.